Risk communication strategies (on listeriosis) for high-risk groups - Maia, Rui Leandro (2018)
Background: Most cases of listeriosis are domestically acquired. Although consumers have a key role in its prevention, it is generally agreed that individuals at higher risk have a low awareness of the infection. Scope and approach: A summary of the scientific information on listeriosis awareness among high-risk groups will be presented. Reasons explaining unawareness and potential strategies to communicate with target groups in a manner that can effectively change risk behaviours reducing the burden of listeriosis will be discussed. Key findings and conclusions: Research efforts are needed in particular experimental studies that can identify which communication factors have a causal effect on peoples’ risk behaviour and how these factors influence the processing of information by consumers.